Heterogeneity and mediating effect in beliefs and attitudes about sleep of cadres: a latent profile analysis - CHEN Zihao, YAO Ailun, FAN Xinwei, LIU Cuiling, SUN Qian, LI Guangming (Xin yixue)
Objective To categorize civil servants’ sleep beliefs and their effects on sleep quality to inform tailored interventions. Methods A total of 507 employed civil servants from Guangzhou were selected and surveyed using the Dysfunctional Beliefs and Attitudes about Sleep Scale （DBAS-16）， Pittsburgh Sleep Quality Index （PSQI）， and Self-Rating Anxiety Scale （SAS）. Latent profile analysis was conducted on cadres’ sleep belief types based on the DBAS-16， and regression mixture analysis was used to explore the factors influencing cadres’ sleep quality and the moderating role of sleep beliefs. Results Analysis identified three sleep belief types: Good Sleep Beliefs （15.2%）， Consequence Bias （57.0%）， and High Worry-Exaggerated Consequences （27.8%）. Significant differences in gender， PSQI， SAS， and stress scores were noted across types（all P < 0.05）. Anxiety and night shifts significantly affected the sleep quality of the High Worry-Exaggerated Consequences type， but not for Good Sleep Beliefs. Conclusion There is heterogeneity in the sleep beliefs of cadres， and sleep beliefs moderate the impact of anxiety and night work on sleep quality， those with fewer biased beliefs are less affected.